2005
DOI: 10.1128/iai.73.9.5554-5567.2005
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Genetic Organization of a Functional Type I Protein Secretion System in Neisseria meningitidis

Abstract: Proteins secreted by Neisseria meningitidis are thought to play important roles in the pathogenesis of meningococcal disease. These proteins include the iron-repressible repeat-in-toxin (RTX) exoprotein FrpC. Related proteins in other pathogens are secreted via a type I secretion system (TOSS), but such a system has not been demonstrated in N. meningitidis. An in silico search of the group B meningococcal genome suggested the presence of a uniquely organized TOSS. Genes encoding homologs of the Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…In agreement with the reports by Klee et al (9) and Wooldridge et al (32), we identified a 1.403-kb locus in the annotated genome sequence of meningococcal strains MC58 and Z2491 that contains an ORF that would encode a TolC-like protein (data not presented). Analysis of the genome sequence flanking this ORF also revealed a closely linked ORF upstream that encodes a protein similar to the HlyD protein of E. coli.…”
Section: Transcription Of the Hlyd-tolc Locus In Meningococcisupporting
confidence: 81%
“…In agreement with the reports by Klee et al (9) and Wooldridge et al (32), we identified a 1.403-kb locus in the annotated genome sequence of meningococcal strains MC58 and Z2491 that contains an ORF that would encode a TolC-like protein (data not presented). Analysis of the genome sequence flanking this ORF also revealed a closely linked ORF upstream that encodes a protein similar to the HlyD protein of E. coli.…”
Section: Transcription Of the Hlyd-tolc Locus In Meningococcisupporting
confidence: 81%
“…In Moraxella species and N. meningitidis, other type I secretion systems have been shown to be involved in secretion of RTX toxin-like exoproteins (Angelos et al, 2003;Wooldridge et al, 2005). In N. meningitidis, the function of these RTX toxin-like exoproteins has remained elusive, but in Moraxella bovis and other c-proteobacteria, they appear to be functional haemolysins (Angelos et al, 2003;Wooldridge et al, 2005). The MFP and ABC components of the type I secretion system are often genetically linked to the exported substrate/toxin.…”
Section: Pathogenesis and Horizontal Gene Transfermentioning
confidence: 99%
“…A third large open reading frame in the transposon (NMC_0891 and a conserved hypothetical protein with significant matches only to N. meningitidis strains) should be examined as a potential substrate for this type I secretion system. The third component necessary for a functional secretion system (TolC) has been identified in N. meningitidis strains (Wooldridge et al, 2005) and is typically not genetically linked to the MFP and ABC components.…”
Section: Pathogenesis and Horizontal Gene Transfermentioning
confidence: 99%
“…The last group of genes identified encodes putative cell surface-localized proteins that include several transporters (e.g., the capsular polysaccharide transport protein CtrD) and a putative hemolysin. In particular, the HlyB and HlyD proteins together with TolC, an outer-membrane channel protein that is encoded in the same putative operon as hlyD, constitute the type I secretion machinery responsible for the secretion of several iron-inducible repeat-in-toxin (RTX) toxin homologues (53)(54)(55)63).…”
Section: Microarray Identification Of Misr-regulated Genesmentioning
confidence: 99%